Anaerob-aerob biofilter evaluation in general hospital of NTB - Nurfitria Hariyani; Sarto Sarto (Berita Kedokteran Masyarakat (BKM), 2018)
Evaluating the use of anaerobic-aerobic biofilter to increase the quality of hospital wastewater Purpose: This study aimed to evaluate the anaerobe-aerobic biofilter systems effectiveness to treating parameters that are affected by the existing units. Methods: This study was conducted with quasi-experimental pretest-posttest approach. Sampling was done in peak hour, intermediate, and minimum wastewater discharge The data analysis used a comparison of quality standards and used the effectiveness level of wastewater treatment through the established formula. Results: The results showed that anaerobic-aerobic biofilter was highly effective in treating total coliform at peak discharge (99.9%), intermediate discharge (83.80%), minimum discharge (99.9%) and effective in processing COD parameters 70.13% at intermediate, and 74.60% minimum discharge. The results also showed anaerobic-aerobic biofilter was quite effective in treating BOD (54.59%) and TSS (50%) and less effective phosphate (40.7%). Data analysis showed that the results of wastewater treatment of provincial hospital in West Nusa Tenggara have met the established quality standards. Conclusion: An anaerobic-aerobic biofilter is effective to increase hospital wastewater to reduce environmental pollution. The impact of this processing will reduce environmental pollution.AbstrakTujuan: Penelitian bertujuan untuk mengevaluasi penggunaan sistem biofilter anaerob-aerob terkait efektivitas dalam mengolah parameter yang dipengaruhi oleh unit yang ada. Metode: Penelitian ini merupakan penelitian quasi experimental dengan menggunakan pendekatan pre-test dan post-test. Pengambilan sampel dilakukan pada saat debit puncak, menengah, dan minimum air limbah. Analisis data menggunakan perbandingan baku mutu dan menggunakan tingkat efektivitas IPAL melalui rumus yang telah ditetapkan. Hasil: Hasil penelitian menunjukkan biofilter anaerob-aerob sangat efektif mengolah total koliform pada debit puncak (99,9%), debit menengah (83,80%), debit minimum (99,9%) dan efektif dalam mengolah parameter COD 70,13% pada debit menengah, dan 74,60% debit minimum. Hasil penelitian menunjukkan biofilter anaerob-aerob cukup efektif dalam mengolah BOD (54,59%) dan TSS (50%) dan kurang efektif mengolah fosfat (40,7%). Analisis data menunjukkan bahwa hasil pengolahan air limbah rumah sakit provinsi NTB telah memenuhi baku mutu yang telah ditetapkan. Simpulan: Biofilter anaerob-aerob efektif meningkatkan kualitas air limbah rumah sakit. Dampak dari proses pengolahan ini akan  mengurangi pencemaran lingkungan.